Processing method and maintenance method for maintenance bonding surface of composite material component
The matrix resin and metal mesh on the surface of composite material components are removed through laser processing technology, the reinforcement fiber layer is retained and the edges of metal mesh are exposed, solving the problems of difficult operation, high cost and environmental pollution in traditional maintenance methods, and achieving efficient, accurate and environmentally friendly maintenance effects of composite material components.
Patent Information
- Application Number
- CN202510512923.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-23
- Publication Date
- 2025-06-27
AI Technical Summary
The prior art is difficult to effectively deal with the maintenance bonding surface of composite components containing metal mesh, especially while ensuring the continuity and maintenance quality of conductive paths, traditional methods have problems such as high operational difficulty, high cost and environmental pollution.
Using laser processing technology, different areas of composite material components are scanned by adjusting laser parameters, the matrix resin and metal mesh on the surface are removed, the reinforcement fiber layer is retained, and the edges of the metal mesh are exposed when necessary to ensure the connection between the old and new metal mesh and the re-establishment of conductive paths.
It realizes efficient, accurate and environmentally friendly maintenance bonding surface processing of composite components, ensures the recovery of conductive properties and the improvement of maintenance quality, while reducing operational difficulty and cost.
Smart Images

Figure CN120206857A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aircraft structural component maintenance, and particularly to a processing method and a maintenance method for the maintenance bonding surface of a composite material component. Background Art
[0002] Fiber-reinforced composite materials have high specific strength and specific modulus, as well as excellent corrosion resistance and fatigue resistance, and are currently widely used in the aerospace field. For example, in the main load-bearing structures of aircraft (such as fuselage and wings) and secondary load-bearing structures (such as rudders and horizontal and vertical tails), fiber-reinforced composite materials are gradually replacing aluminum alloys. Compared with traditional aluminum alloy materials, fiber-reinforced composite materials have lower thermal conductivity and electrical conductivity. During the continuous operation of the aircraft, it is inevitable to be struck by lightning, and the Joule heat generated by lightning will cause serious irreversible damage to the composite material components. Therefore, metal meshes, such as copper meshes and aluminum meshes, are usually added to the composite material components as lightning protection layers. The metal mesh can enhance the electrical conductivity of the component, so that most of the lightning current stays on the external structure and flows out quickly, without causing serious damage to the composite material component.
[0003] During the production, operation and maintenance of aircraft, the composite material components will inevitably suffer various forms of impact damage, such as tool dropping, bird strike, hail impact, gravel impact, etc. These impacts usually cause visible or invisible damage to the internal structure of the material, such as microscopic damages like matrix cracking, delamination, debonding and fiber fracture, thereby degrading its structural and mechanical properties and shortening its service life. In view of the overall development trend of composite material structures, directly replacing damaged components faces problems such as high operation difficulty, high cost and time consumption. Developing reliable composite material maintenance technology is crucial for ensuring the flight safety and continuous airworthiness of aircraft.
[0004] The maintenance of aircraft composite material structures not only needs to restore the original mechanical properties, but also needs to maintain a good aerodynamic shape. According to the composite material structure repair process specified in the Aircraft Structural Repair Manual (SRM), common maintenance methods include scarf joint and step joint bonding. The manual requires that an additional additional layer needs to be bonded to the surface of the material to be repaired to ensure the repair quality. Therefore, maintenance personnel need to first remove the matrix resin and the additional metal mesh on the surface of the first layer of fibers of the composite material component to be repaired.
[0005] The repair bonding surface processing techniques for traditional composite material components mainly include manual grinding and milling. However, the pneumatic grinding process highly depends on the operation skills of the maintenance personnel, making it difficult to ensure the processing accuracy and surface quality, thus affecting the repair effect. During the milling process, a large amount of dust is inevitably generated, posing potential hazards to the health of the operators and the environment. In addition, lightning protection nets are usually made of mesh-shaped metal materials with high electrical conductivity, hardness, and toughness. The hardness and toughness of these materials make the grinding process difficult and require special tools and techniques. The grid structure of the metal mesh also increases the complexity of grinding. The small gaps and irregular shapes of the grids make it difficult to evenly reach all areas using standard grinding tools and techniques, especially at the grid intersections and corners. Summary of the Invention
[0006] Based on this, it is necessary to provide a processing method and a repair method for the repair bonding surface of a composite material component containing a metal mesh.
[0007] One of the objectives of the present invention is to provide a processing method for the repair bonding surface of a composite material component, and the solution is as follows:
[0008] A processing method for the repair bonding surface of a composite material component, the composite material component includes a matrix resin, a reinforcing fiber layer, and a metal mesh, the reinforcing fiber layer and the metal mesh are stacked and wrapped by the matrix resin; the processing method includes the following steps:
[0009] Use a laser with the first parameter to scan the first area of the composite material component to remove the matrix resin and the metal mesh on the surface of the first area, and retain the reinforcing fiber layer under the metal mesh;
[0010] Use a laser with the second parameter to scan the second area of the composite material component to remove the matrix resin on the surface of the second area, and retain the metal mesh and the reinforcing fiber layer of the second area; the second area is adjacent to the first area.
[0011] In one embodiment, the first parameter includes: using a nanosecond laser with a wavelength of 500 - 1200 nm, a power of 100 W - 150 W, a scanning speed of 3000 mm / s - 4500 mm / s, a line spacing of 0.04 mm - 0.06 mm, and a pulse width of 25 ns - 70 ns.
[0012] In one embodiment, the second parameter includes: using a nanosecond laser with a wavelength of 500 - 1200 nm, a power of 100 W - 150 W, a scanning speed of 1500 mm / s - 3000 mm / s, a line spacing of 0.01 mm - 0.04 mm, and a pulse width of 50 ns - 100 ns.
[0013] In one embodiment, the second region is disposed to surround the first region.
[0014] In one embodiment, the second region is located on opposite sides of the first region.
[0015] In one embodiment, an ablation protection layer is disposed around the first region and the second region before laser scanning.
[0016] In one embodiment, the composite material member is subjected to air suction cleaning during laser scanning.
[0017] In one embodiment, the composite material member is an aircraft secondary structural member.
[0018] In one embodiment, the material of the matrix resin is at least one of epoxy resin, bismaleimide resin, polyimide, and cyanate resin.
[0019] In one embodiment, the material of the reinforcing fiber layer is at least one of carbon fiber, glass fiber, and basalt fiber.
[0020] In one embodiment, the material of the metal mesh is at least one of copper and its alloys, aluminum, and iron and its alloys.
[0021] Another object of the present invention is to provide a method for repairing a composite material member, and the solution is as follows:
[0022] A method for repairing a composite material member includes the following steps:
[0023] The repair bonding surface is processed by the processing method described in any of the above embodiments;
[0024] A repair patch is bonded to the repair bonding surface.
[0025] Compared with the traditional technology, the above processing method and repair method for the repair bonding surface of the composite material member have the following beneficial effects:
[0026] The processing method and repair method for the repair bonding surface of the above composite material component scan the first area and the second area of the composite material component by adjusting the laser parameters, remove the matrix resin and the metal mesh on the surface of the first area, and remove the matrix resin on the surface of the second area, exposing the metal mesh at the inner edge of the second area, so as to ensure that the newly inlaid metal mesh is connected to the original metal mesh of the material, and re - establish the conductive path on the material surface. The laser processing technology can not only ensure the uniformity and consistency of the processed area, has the characteristics of green, high - efficiency and environmental protection, but also can accurately process different shapes according to the design scheme, with the characteristics of freedom, flexibility, strong designability and strong adaptability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 FIG. is a schematic diagram of the laser scanning area in the processing method for the repair bonding surface of a composite material component according to an embodiment;
[0028] Figure 2 In (a) is the 3D confocal microscope characterization structure diagram of the material surface after laser treatment; Figure 2 In (b) is the electron microscope image of the material surface after laser treatment; Figure 2 In (c) is a schematic diagram of the micron / sub - micron mechanical interlocking structure formed on the material surface after laser treatment;
[0029] Figure 3 FIG. is the optical microscope image after scanning the first area of the composite material component in Example 1;
[0030] Figure 4 FIG. is the optical microscope image after scanning the second area of the composite material component in Example 1. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0031] In order to make the above - mentioned objects, features and advantages of the present invention more obvious and understandable, the following detailed description of the specific embodiments of the present invention will be given with reference to the accompanying drawings. Many specific details are set forth in the following description in order to fully understand the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without departing from the connotation of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed below.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the technical field to which this invention belongs. The terms used herein in the description of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0033] In the description of the present invention, it should be understood that the orientation or positional relationship indicated by the terms "center", "longitudinal", "transverse", "length", "width", "thickness", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. is based on the orientation or positional relationship shown in the drawings, and is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and thus cannot be construed as a limitation on the present invention.
[0034] In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be construed as indicating or implying relative importance or implicitly specifying the quantity of the indicated technical features. Thus, the features defined with "first" and "second" may explicitly or implicitly include at least one of such features. In the description of the present invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise specifically and clearly defined.
[0035] To reduce the lightning strike damage to an aircraft, a metal mesh, such as a copper mesh, an aluminum mesh, etc., is usually added to a composite material member as a lightning protection layer. The metal mesh can enhance the electrical conductivity of the member, causing most of the lightning current to stay on the external structure and flow out quickly, without causing serious damage to the composite material member.
[0036] The present invention provides a method for processing a repair bonding surface of a composite material member for a composite material member containing a metal mesh. The composite material member is, for example, an aircraft structural member, more specifically an aircraft secondary structural member.
[0037] Among them, the composite material member includes a matrix resin, a reinforcing fiber layer, and a metal mesh. The reinforcing fiber layer and the metal mesh are stacked and wrapped by the matrix resin.
[0038] Optionally, the material of the matrix resin may be, but is not limited to, at least one of epoxy resin, bismaleimide resin, polyimide, and cyanate resin.
[0039] Optionally, the material of the reinforcing fiber layer may be, but is not limited to, at least one of carbon fiber, glass fiber, and basalt fiber.
[0040] Optionally, the material of the metal mesh may be, but is not limited to, at least one of copper and its alloys, aluminum, and iron and its alloys.
[0041] The method for processing the repair bonding surface of the composite material member in an embodiment includes the following steps:
[0042] Step S1, as Figure 1As shown, a laser using a first parameter is scanned over a first region 110 of a composite member to remove the matrix resin and the metal mesh on the surface of the first region 110, and the reinforcing fiber layer under the metal mesh is retained.
[0043] In step S1, by reasonably adjusting the laser parameters, the interface temperature can be effectively controlled to reach the matrix decomposition threshold without reaching the fiber damage threshold, realizing the interface separation of heterogeneous materials and facilitating the removal of the matrix resin and the metal mesh in the first region 110. This process simultaneously involves photothermal-induced thermal ablation, micro-blasting, and thermal vibration effects. Therefore, only a relatively low laser energy is required to slightly decompose the closely adhered interface to achieve the removal of the target material.
[0044] In step S1, the laser preferably has parameters of a low horizontal and vertical overlap rate, a low total laser energy density, and a high single-pulse laser energy density.
[0045] Among them, the calculation formula for the total energy density (Et): Et = laser power / (scanning speed × line spacing).
[0046] The calculation formula for the single-pulse energy density (Es): Es = laser power / (frequency × spot area).
[0047] In step S1, the laser, for example, adopts parameters of medium power, high speed, high spacing, low frequency, and low pulse width to achieve a low horizontal and vertical overlap rate, a low total energy density, and a high single-pulse energy density.
[0048] Preferably, the absorption rate of the matrix resin for the adopted laser is relatively low, for example, less than 5%. In some examples, in step S1, the laser used is a nanosecond laser. Further, the wavelength of the laser is 500 - 1200 nm. For example, the absorption rate of a common epoxy resin matrix for a 1064 nm band laser is less than 5%.
[0049] In some examples, in step S1, a nanosecond pulse laser is used for scanning. Further, a nanosecond infrared fiber pulse laser is used, including but not limited to femtosecond lasers, picosecond lasers, Nd:YAG lasers, semiconductor lasers, fiber lasers, etc.
[0050] In step S1, the laser scanning path filling includes but is not limited to parallel line filling, bow-shaped line filling, concentric circle filling, loop line filling, Z-shaped line filling, etc.
[0051] In some examples, in step S1, the power of the laser used is 100W - 150W, specifically, for example, 100W, 105W, 110W, 115W, 120W, 125W, 130W, 135W, 140W, 145W, 150W, etc., or the range between any two of the above values.
[0052] In some of these examples, in step S1, the scanning speed of the laser used is 3000 mm / s to 4500 mm / s, specifically for example 3000 mm / s, 3200 mm / s, 3400 mm / s, 3600 mm / s, 3800 mm / s, 4000 mm / s, 4200 mm / s, 4500 mm / s, etc., or the range between any two of the above values.
[0053] In some of these examples, in step S1, the line spacing of the laser used is 0.04 mm to 0.06 mm, specifically for example 0.04 mm, 0.042 mm, 0.044 mm, 0.046 mm, 0.048 mm, 0.05 mm, 0.052 mm, 0.054 mm, 0.056 mm, 0.058 mm, 0.06 mm, etc., or the range between any two of the above values.
[0054] In some of these examples, in step S1, the pulse width of the laser used is 25 ns to 70 ns, specifically for example 25 ns, 30 ns, 35 ns, 40 ns, 45 ns, 50 ns, 55 ns, 60 ns, 65 ns, 70 ns, etc., or the range between any two of the above values.
[0055] In step S1, the shape of the first region 110 can be, but is not limited to, circular, oval, rectangular, etc.
[0056] Step S2, use the laser with the second parameter to scan the second region 120 of the composite material component to remove the matrix resin on the surface of the second region 120, and retain the metal mesh and the reinforcing fiber layer in the second region 120. The second region 120 is adjacent to the first region 110.
[0057] In some of these examples, the second region 120 is arranged to surround the first region 110.
[0058] In some of these examples, the second region 120 is located on opposite sides of the first region 110.
[0059] In step S2, the laser preferably has parameters of high horizontal and vertical overlap rates, high total laser energy density, and high single-pulse laser energy density. This helps the heat to quickly reach the matrix decomposition point. The purpose of step S2 is to expose the metal mesh at the inner edge of the second region 120 to ensure that the newly inlaid metal mesh is connected to the original metal mesh of the material, and to re-establish the conductive path on the material surface. This step is crucial for the functions of the composite material such as lightning protection and electromagnetic resistance.
[0060] In some of these examples, in step S2, the laser used is a nanosecond laser. Further, the wavelength of the laser is 500 - 1200 nm.
[0061] In some of these examples, in step S2, a nanosecond pulsed laser is used for scanning. Further, a nanosecond infrared fiber pulsed laser is used, including but not limited to femtosecond lasers, picosecond lasers, Nd:YAG lasers, semiconductor lasers, fiber lasers, etc.
[0062] In step S2, the laser scanning path filling includes but not limited to parallel line filling, bow-shaped line filling, concentric circle filling, figure-eight line filling, Z-shaped line filling, etc.
[0063] In some of these examples, in step S2, the power of the laser used is 100 W - 150 W, specifically for example 100 W, 105 W, 110 W, 115 W, 120 W, 125 W, 130 W, 135 W, 140 W, 145 W, 150 W, etc., or the range between any two of the above values.
[0064] In some of these examples, in step S2, the scanning speed of the laser used is 1500 mm / s - 3000 mm / s, specifically for example 1500 mm / s, 1700 mm / s, 1900 mm / s, 2100 mm / s, 2300 mm / s, 2500 mm / s, 2700 mm / s, 2900 mm / s, 3000 mm / s, etc., or the range between any two of the above values.
[0065] In some of these examples, in step S2, the line spacing of the laser used is 0.01 mm - 0.04 mm, specifically for example 0.01 mm, 0.015 mm, 0.02 mm, 0.025 mm, 0.03 mm, 0.035 mm, 0.04 mm, etc., or the range between any two of the above values.
[0066] In some of these examples, in step S2, the pulse width of the laser used is 50 ns - 100 ns, specifically for example 50 ns, 55 ns, 60 ns, 65 ns, 70 ns, 75 ns, 80 ns, 85 ns, 90 ns, 95 ns, 100 ns, etc., or the range between any two of the above values.
[0067] In step S3, a laser with a third parameter is used to scan the first region 110 and the second region 120 to remove the residual pyrolysis products on the first region 110 and the second region 120, obtaining a repaired bonding surface.
[0068] In step S3, the first region 110 and the second region 120 are scanned with a laser using a third parameter to remove a small amount of pyrolysis products on the fiber surface, such as carbon deposits, pyrolysis oil, etc. If there is residual resin on the first region 110 and the second region 120, it can also be removed together, and a clean, complete, and undamaged fiber surface to be bonded can be obtained.
[0069] In step S3, the laser preferably has a lower energy density, which helps to avoid oxidative damage to the fibers in the air environment.
[0070] In step S3, the laser parameters preferably have a high horizontal and vertical overlap rate and a low total laser energy density.
[0071] In some of the examples, in step S3, the laser used is a nanosecond laser. Further, the wavelength of the laser is 500 nm to 1200 nm. In some of the examples, in step S3, the wavelength of the laser is 1064 nm.
[0072] In some of the examples, in step S3, a nanosecond pulse laser is used for scanning. Further, a nanosecond infrared fiber pulse laser is used, including but not limited to Nd:YAG lasers, semiconductor lasers, fiber lasers, etc.
[0073] In step S3, the laser scanning path filling includes but not limited to parallel line filling, bow-shaped line filling, concentric circle filling, loop line filling, Z-shaped line filling, etc.
[0074] In some of the examples, in step S3, the power of the laser used is 50 W to 100 W, specifically, for example, 50 W, 55 W, 60 W, 65 W, 70 W, 75 W, 80 W, 85 W, 90 W, 95 W, 100 W, etc., or a range between any two of the above values.
[0075] In some of the examples, in step S3, the scanning speed of the laser used is 2000 mm / s to 4000 mm / s, specifically, for example, 2200 mm / s, 2500 mm / s, 2800 mm / s, 3000 mm / s, 3200 mm / s, 3400 mm / s, 3600 mm / s, 3800 mm / s, 4000 mm / s, etc., or a range between any two of the above values.
[0076] In some of these examples, in step S3, the line spacing of the laser used is 0.01 mm to 0.03 mm, specifically for example 0.01 mm, 0.012 mm, 0.014 mm, 0.016 mm, 0.018 mm, 0.02 mm, 0.022 mm, 0.024 mm, 0.026 mm, 0.028 mm, 0.03 mm, etc., or the range between any two of the above values.
[0077] In some of these examples, in step S3, the pulse width of the laser used is 25 ns to 50 ns, specifically for example 25 ns, 30 ns, 35 ns, 40 ns, 45 ns, 50 ns, etc., or the range between any two of the above values.
[0078] In step S3, the shape of the first region 110 can be but is not limited to circular, elliptical, rectangular, etc.
[0079] In some of these examples, in step S3, the number of laser scans is 1 to 10 times, specifically for example 1 time, 2 times, 4 times, 6 times, 8 times.
[0080] In some of these examples, before laser scanning, an ablation protection layer is provided on the periphery (the third region 130) of the first region 110 and the second region 120. The ablation protection layer can be, for example, a high-temperature fireproof tape. By providing the ablation protection layer in the third region 130, the resin degradation in the non-processing area caused by resin ablation can be avoided, and the processing accuracy can be improved and the integrity of the component can be protected.
[0081] In some of these examples, during laser scanning, the composite component is cleaned by suction, for example, a fume purification device is used to adsorb the processing area, which can avoid accidental ablation of the material caused by unstable flame. The suction cleaning operation can also quickly remove the pyrolysis gas generated by resin degradation in the laser processing area. The pyrolysis gas is flammable, and if not absorbed in time, it will cause combustion in the processing area, thereby causing damage to the carbon fiber. In addition, a large amount of heat is carried away during the resin evaporation process, and timely use of the suction system to remove the pyrolysis gas helps to reduce the peak temperature in the processing area.
[0082] Taking an infrared nanosecond pulsed laser with a wavelength of 500 to 1200 nm as an example, according to Planck's equation, the single-photon energy in the wavelength band of λ = 500 to 1200 nm is about 1.17 eV, which is difficult to directly break the C-C bond (3.45 eV) and C-O bond (3.38 eV) in the resin (such as but not limited to epoxy resin). Therefore, most of the laser energy directly penetrates the surface resin and acts on the surface of the reinforcing fiber (such as but not limited to carbon fiber). This unique interaction mode helps to separate the two heterogeneous materials from the inside.
[0083] Using a laser with a specific wavelength band can achieve directional micro - heating at the interface between the metal mesh, resin matrix, and fiber. Meanwhile, the pyrolysis vapor will generate micro - explosions due to internal space constraints, promoting the peeling between the metal mesh, resin matrix, and fiber. In addition, there are significant differences in the physical properties of the three materials, namely the resin matrix, metal mesh, and fiber, and vibration caused by thermal expansion will also occur at the interface to be separated.
[0084] In summary, in terms of mechanism, the peeling mechanism utilized in the present invention is mainly the complex synergistic effect of thermal ablation, micro - explosion, and thermal vibration. Based on the above laser - material interaction mechanism, the present invention only needs to pyrolyze and remove a small amount of interfacial resin to achieve synchronous peeling of the resin and the metal mesh.
[0085] Adopting one - time peeling is significant because bonding repair highly emphasizes the quality of the exposed fiber surface, including surface cleanliness, fiber integrity, etc. Excessive pyrolysis reactions are difficult to ensure the quality of the fiber surface. For example, using high laser energy to burn a large amount of resin will cause fiber damage and generate a large amount of impurities. Therefore, adopting the one - time peeling process reduces the process difficulty of subsequent cleaning, reduces the overall process energy consumption, and ensures the consistency of the fiber surface quality.
[0086] The bonding mechanism is often used to explain the relationship between surface physical and chemical properties and bonding performance. Among them, mechanical interlocking, wetting adsorption, and chemical bonding are three common bonding theories.
[0087] As Figure 2 shown in (a) and (b) therein, it is found that when the resin on the surface of the composite material component is completely removed by the laser, complete fiber tows are exposed, obtaining a directional fiber monofilament arrangement texture (gully - like texture) and a fiber multifilament braiding texture (equidistant - spaced pit texture), forming an ordered surface pattern structure.
[0088] Laser treatment can promote the mechanical interlocking effect. After laser treatment, a periodic structure (LIPSS) is formed on the surface of the composite material component. The high - aspect - ratio linear grooves formed by the gaps between fiber monofilaments have a longitudinal length of about 2.1 mm, which is the length of the braiding area; the maximum width of the transverse gap is 6 μm, and the minimum can reach 0.8 μm (sub - micron level). In addition, the resin - rich area at the equally - spaced fiber braiding is ablated by the laser to form a cavity with a depth of about 67.8 μm (micron level).
[0089] Laser treatment can promote the wetting adsorption effect. As Figure 2 shown in (c) therein, after laser treatment, the pits formed on the surface of the composite material component are filled with the adhesive during bonding, playing a "micron - level anchoring role", and the gaps between the fibers are infiltrated by the adhesive, playing a "sub - micron - level mechanical interlocking role".
[0090] The uniformity of the surface structure formed by traditional pneumatic grinding is poor, and there are a large number of resin residues and fiber fractures. Its mechanical interlocking and infiltration adsorption effects are weaker than those of the above laser treatment process.
[0091] The processing method of the repair bonding surface of the composite material component described above scans the first region and the second region of the composite material component by adjusting the laser parameters, removes the matrix resin and the metal mesh on the surface of the first region, and removes the matrix resin on the surface of the second region, exposing the metal mesh at the inner edge of the second region to ensure that the newly inlaid metal mesh is connected to the original metal mesh of the material, and re - establishes the conductive path on the material surface. Then, adjust the laser parameters to scan the first region and the second region to remove the residual pyrolysis products on the first region and the second region, and obtain a clean and complete repair bonding surface. The laser treatment process can not only ensure the uniformity and consistency of the treatment area, has the characteristics of green, high - efficiency and environmental protection, but also can accurately process different shapes according to the design scheme, with the characteristics of freedom, flexibility, strong designability and strong adaptability.
[0092] Furthermore, the present invention also provides a repair method for composite material components.
[0093] The repair method of the composite material component in an embodiment includes the following steps:
[0094] Obtain the repair bonding surface by processing through the processing method of any of the above examples;
[0095] Bond a repair patch on the repair bonding surface.
[0096] The following provides specific embodiments to further illustrate the present invention. The present invention provides the following specific embodiments for better further understanding of the present invention, which are not limited to the specific implementation manners and do not constitute a limitation to the protection scope of the present invention.
[0097] Embodiment 1
[0098] The processing method of the repair bonding surface of the composite material component provided in this embodiment includes the following steps:
[0099] Step 1, preparation work.
[0100] According to the repair design, stick high - temperature fire - proof tape around the target processing area on the surface of the composite material component.
[0101] Step 2, remove the matrix resin and metal mesh in the first region 110.
[0102] Use a 1064nm nanosecond flat - top fiber laser to scan the first region 110 of the composite material component. As Figure 3As shown, the matrix resin and the metal mesh on the surface of the first region 110 are removed, and the reinforcing fiber layer under the metal mesh is retained. The laser power is 100 W, the scanning speed is 4000 mm / s, the line spacing is 0.04 mm, and the pulse width is 25 ns.
[0103] After the laser scanning is completed, the metal mesh and the resin layer are integrally peeled off from the surface of the composite material component using tweezers.
[0104] Step 3: Remove the matrix resin in the second region 120.
[0105] A 1064 nm nanosecond flat-top fiber laser is used to scan the second region 120 of the composite material component. The second region 120 is located on opposite sides of the first region 110. As Figure 4 shown, the matrix resin on the surface of the second region 120 is removed, and the metal mesh and the reinforcing fiber layer of the second region 120 are retained. The laser power is 200 W, the scanning speed is 3000 mm / s, the line spacing is 0.05 mm, and the pulse width is 100 ns.
[0106] Step 4: Laser clean the residues on the surface of the area to be bonded.
[0107] A 1064 nm nanosecond flat-top fiber laser is used to scan the first region 110 and the second region 120. The residues on the surface of the area to be bonded are laser cleaned. The laser power is 100 W, the scanning speed is 3000 mm / s, the line spacing is 0.02 mm, and the pulse width is 25 ns.
[0108] Pneumatic grinding has the following disadvantages:
[0109] The metal material used for the lightning protection net has high hardness and toughness. The hardness, toughness, and grid structure of the material increase the grinding difficulty. General grinding tools are difficult to uniformly process all areas, especially the grid intersections and corners. It highly depends on the proficiency of manual operation, and it is difficult to ensure the machining dimensional accuracy, uniformity, and consistency, which affects the repair effect. In addition, pneumatic grinding is inefficient, increasing the out-of-service repair cost of the aircraft operating on the route.
[0110] Milling has the following disadvantages:
[0111] Inevitably, a large amount of dust is generated, which is harmful to the health of operators and the environment. As a contact mechanical processing method, milling will cause a large number of fibers in the composite material components to break due to mechanical action, easily causing interface failure on the bonding surface, and then resulting in problems such as debonding, and the repair effect is not good. In addition, contact processing is prone to tool wear, which will not only reduce the machining accuracy, but also increase additional costs and time costs.
[0112] The present invention can achieve the following beneficial effects:
[0113] 1. Non-contact laser processing avoids the generation of dust in traditional manual grinding, and has the characteristics of being green, efficient, and environmentally friendly.
[0114] 2. Based on multiple synergistic effects, the target material is peeled off and removed, enabling the entire process to only require adjusting the laser parameters without any auxiliary means, significantly reducing the overall energy consumption of the process, and having the characteristics of energy conservation and high efficiency.
[0115] 3. The slight decomposition interface realizes the peeling and removal of the material, avoiding the by-products generated by the thermal decomposition of the resin, and obtaining excellent surface quality (including cleanliness and integrity) of the surface to be bonded.
[0116] 4. The oxygen-free thermal decomposition mode achieved by penetrating the surface resin matrix and heating the internal interface makes the structure of the fiber surface intact and undamaged after treatment.
[0117] 5. The laser treatment method retains the fiber micron and sub-micron level structures, enhances the effects of mechanical interlocking and infiltration adsorption, and improves the bonding effect after repair.
[0118] 6. The laser process can accurately process different shapes according to the design scheme, such as circular, elliptical, rectangular, etc., and has the advantages of being free, flexible, highly designable, and adaptable.
[0119] The technical features of the above-described embodiments can be combined arbitrarily. For the sake of brevity of description, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, it should be considered as falling within the scope described in this specification.
[0120] The above-described embodiments only represent several implementation manners of the present invention, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the invention patent. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present invention, several modifications and improvements can still be made, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent should be subject to the appended claims, and the specification can be used to explain the content of the claims.
Claims
1. A method for processing a repair bonding surface of a composite material component, wherein the composite material component comprises a matrix resin, a reinforcing fiber layer and a metal mesh, wherein the reinforcing fiber layer and the metal mesh are stacked and wrapped by the matrix resin; characterized in that: The processing method comprises the following steps: Scanning a first region of the composite material component using a laser with a first parameter to remove the matrix resin and the metal mesh on the surface of the first region and retain the reinforcing fiber layer under the metal mesh; A laser with a second parameter is used to scan a second region of the composite material component to remove the matrix resin on the surface of the second region and retain the metal mesh and the reinforcing fiber layer in the second region; the second region is connected to the first region.
2. The processing method according to claim 1, characterized in that: The first parameters include: wavelength of 500-1200nm, power of 100W-150W, scanning speed of 3000mm / s-4500mm / s, line spacing of 0.04mm-0.06mm, and pulse width of 25ns-70ns.
3. The processing method according to claim 1, characterized in that: The second parameters include: wavelength of 500-1200nm, power of 100W-150W, scanning speed of 1500mm / s-3000mm / s, line spacing of 0.01mm-0.04mm, and pulse width of 50ns-100ns.
4. The processing method according to any one of claims 1 to 3, characterized in that: The second area is arranged around the first area; or The second region is located on two opposite sides of the first region.
5. The processing method according to any one of claims 1 to 3, characterized in that: Before laser scanning, an ablation protection layer is disposed around the first region and the second region.
6. The processing method according to any one of claims 1 to 3, characterized in that: The composite material component is cleaned by suction during the laser scanning process.
7. The processing method according to any one of claims 1 to 3, characterized in that: The composite material component is an aircraft secondary structure component.
8. The processing method according to any one of claims 1 to 3, characterized in that: The material of the matrix resin is at least one of epoxy resin, bismaleimide resin, polyimide and cyanate resin; and / or The material of the reinforcing fiber layer is at least one of carbon fiber, glass fiber and basalt fiber.
9. The processing method according to any one of claims 1 to 3, characterized in that: The material of the metal mesh is at least one of copper and its alloys, aluminum, iron and their alloys.
10. A method for repairing a composite material component, characterized in that: The following steps are involved: The repair adhesive surface is obtained by processing using the processing method described in any one of claims 1 to 9; A repair sheet is bonded on the repair bonding surface.